Design and Testing of Twin-Disk Friction Torque Test Rig Using Quality Function Deployment and Function Analysis Methods Approach - Dedison Gasni; Roihan Ashari; Hendri Yanda; Nabil Hendardi (METAL: Jurnal Sistem Mekanik dan Termal, 2026)
Fatigue failure is the most common failure in gears besides failure due to friction and wear on the surface of the gear. To determine the failure phenomenon that occurs in gears, testing can be done on the gear, but the testing will be expensive. So it is necessary to test on a laboratory scale to understand the failure mechanism of gears by designing and making a twin-disk friction torque test rig. The design process used an approach model developed by the National Aeronautics and Space Administration (NASA) to maximize user desires with the Quality Function Deployment (QFD) method approach and to be able to meet technical needs with the Function Analysis Methods (FAM) approach. The results of the design that has been done provide the design of a twin-disk friction torque test rig that has met user needs and, from the test results of the test rig's performance, has met the expected functional requirements as a test tool. From the results of tests that have been carried out on changes in load and slip ratio, the friction torque will increase with increasing load and slip ratio. While the friction coefficient will decrease with increasing load, and vice versa, with increasing slip ratio, the friction coefficient will increase. The data generated from the measurements are consistent, so the test rig can be used to measure friction torque.